\(x+2\dfrac{1}{4}=4\dfrac{5}{6}\)
\(x=4\dfrac{5}{6}-2\dfrac{1}{4}\)
\(x=4+\dfrac{5}{6}-2-\dfrac{1}{4}\)
\(x=2+\dfrac{7}{12}\)
\(x=\dfrac{31}{12}\)
_____________
\(9\dfrac{3}{5}-x=3\dfrac{3}{8}\)
\(x=9\dfrac{3}{5}-3\dfrac{3}{8}\)
\(x=9+\dfrac{3}{5}-3-\dfrac{3}{8}\)
\(x=6+\dfrac{9}{40}\)
\(x=\dfrac{249}{40}\)
\(x+2\dfrac{1}{4}=4\dfrac{5}{6}\)
\(=>x+\dfrac{9}{4}=\dfrac{29}{6}\)
\(=>x=\dfrac{29}{6}-\dfrac{9}{4}=\dfrac{58}{12}-\dfrac{27}{12}\)
\(=>x=\dfrac{31}{12}\)
_______
\(9\dfrac{3}{5}-x=3\dfrac{3}{8}\)
\(=>\dfrac{48}{5}-x=\dfrac{27}{8}\)
\(=>x=\dfrac{48}{5}-\dfrac{27}{8}=\dfrac{384}{40}-\dfrac{135}{40}\)
\(=>x=\dfrac{249}{40}\)